A review: muscle discomfort of police officers in vehicles - Karuppiah, Karmegam; Mohammad Yusof, Nur Athirah Diyana; Md Tamrin, Shamsul Bahri; How, Vivien; Rasdi, Irniza; Sambasivam, Sivasankar; Md Isa, Mohd Hafzi (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2019)
This paper studies the muscle discomfort among police officers when carrying out their work. The objective of this study is to give a basic introduction of ergonomic problems in among police officers and risk controls in relation to minimize the ergonomics risk factors. This paper gives quick review of muscle discomfort problems and prevalence of musculoskeletal disorders (MSD) among police officer. An ergonomic application has been purposed in the literature to solve the problem related with design of mechanical.